Religious and spiritual support in the conception of nurses and families of critical patients: a cross-sectional study - Petherson Mendonça dos Santos; Kirliane de Sousa Rodrigues; Lucas Andrade Pinheiro; Breno de Sousa Santana; Michelle Zampieri Ipólito; Marcia Cristina da Silva Magro (SciELO, 2021)
ABSTRACT Objective: To assess the religious and spiritual support in critical care according to the conception of patients' family members and nurses. Method: This is a quantitative cross-sectional study conducted with nurses and relatives of patients admitted to intensive care units. Sociodemographic data were collected and a questionnaire on religiosity and spirituality was applied to family members and the Spirituality and Spiritual Care Rating Scale to nurses. The results with p ≤ 0.05 were significant. Results: Sample consisted of intensive care nurses (n = 22) and family members (n = 61). Intensive care nurses stated that they can provide spiritual care (p = 0.03). Of the family members, 88.5% believed that religiosity and spirituality help in coping with difficult times, highlighting prayer as part of care for critically ill patients (p = 0.02). Conclusion: Nurses and family members recognized religious/spiritual support as significant to the process of caring for critically ill patients, even though professional qualification is required for greater integration of this support in daily intensive care.